Police response to individuals displaying suicidal or self‐harming behaviours: An integrative review. (16th October 2018) - Chidgey, Kelly; Procter, Nicholas; Baker, Amy; Grech, Carol
Abstract: Police are increasingly being called upon to respond to people experiencing suicidal crisis. Such incidents are a challenging aspect of modern policing. This paper reports on an integrative review study that aimed to investigate police responses to individuals displaying suicidal or self‐harming behaviours. Six electronic databases were searched for peer‐reviewed articles published between 2007 and 2017 relating to police responses to individuals in suicidal crisis. The review identified 12 studies that met the inclusion criteria. A content analysis was conducted to identify and describe the key characteristics emerging from the literature, which identified four themes: "characteristics of individuals"; "the use of violence and weapons"; "contact with police prior to suicide"; and, "police officer training". Findings from this study indicate that individuals involved in incidents of suicidal and self‐harm crisis with police are often male, aged between 35 and 40 years, single and/or having relationship issues, with a history of mental health issues and in recent contact with police prior to the incident of suicidal crisis—either as a victim or a perpetrator. The results highlight that large proportions of individuals in suicidal crisis within a community located incident are likely to present with violent or aggressive behaviour and in many situations are armed with a weapon used to either threaten or injure police and/or bystanders or self‐harm. Training and education can have a positive impact from the perspective of police responding to individuals in suicidal crisis. Limitations in the current evidence are identified and implications for future research are outlined.